A novel vardenafil analog in a healthcare product: Preparation, characterization, and quantification - Jintao Xia; Wanqin Wu; Feng Jiang; Songsong Zhu (Heliyon, 2023)
Objective: This study is aimed to develop a qualitative and quantitative method to detect a novel vardenafil analogue from a healthcare product, which is claimed to enhance sexual function. Method: The unknown compound was detected by non-targeted screening using ultra-high performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS). MS2 spectra showed that the characteristic fragment ions of this unknown compound were highly similar to those of vardenafil. This compound was subsequently isolated by silica gel column chromatography and characterized by 1D (dimension) and 2D nuclear magnet resonance (NMR) specta, ultra-violet (UV) spectra, and fourier transform infrared (IR) spectra. A quantitative method for analyzing this identified compound in various healthcare product was developed based on high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS).Results: The unknown compound was identified as 2-(5-((4-ethylpiperazin-1-yl)sulfonyl)-2-propoxyphenyl)-5-methyl-7-propylimidazo.[5,1-f] [1,2,4]triazin-4(3H)-one based on the spectroscopic data. Quantitative results revealed that the matrix calibration curves of this compound had a good linear ranges of 2～50 ng/mL in pressed candy (R2 = 0.998), energy coffee (R2 = 0.999), and health wine (R2 = 0.997), respectively. The matrix effects, recoveries, and limit of quantitation (LOQ) of this compound all met the requirements of quantitative validation. Finally, the content of this compound in 5 batches of positive samples ranged from 1.24 to 7.20 g/kg. Conclusion: This study identified a novel vardenafil analog from a healthcare product and named it O-propyl vardenafil, and this compound was distinguished from vardenafil by the replacement of the ethyl group with a propyl group at the aryl alkyl ether moiety. Our developed quantitative method could meet practical needs. The high positive rate (16.67%) in 30 samples suggested that the related regulators should be alert to O-propyl vardenafil in routine test since it has not been detected ever before.